Efficacy of stimulant medication treatment of attention deficit hyperactivity disorder in preschool-aged children. - Musten, Lynette Monteiro. (University of Ottawa (Canada), 1996)
Longitudinal information indicates children who present with 'hard-to-manage' or problematic behaviours at a very young age are at risk for on-going difficulties with parents, peers and in school. However, there are few interventions that have demonstrated effectiveness in ameliorating the symptoms that appear to be precursors of Attention Deficit Hyperactivity Disorder (ADHD). Despite the use of methylphenidate (MPH) to treat Attention Deficit Hyperactivity Disorder in very young children, there is little information related to its efficacy within this age group. This study examined the effectiveness of medication on the cognitive, behavioural and interpersonal domains of young children who were diagnosed with ADHD. The children were assessed using cognitive measures, behavioural ratings scales and interactive measures assessing child compliance and attention. Furthermore, the effect of the children's medication status on parental style, skills and stress also were assessed using behavioural observations of parent and child engaged in interactive tasks. Changes in parental style, skills and stress were evaluated. Twenty-four children, aged 4 to 6 years, diagnosed with ADHD, participated in a double-blind, placebo-controlled study evaluating the efficacy of 0.3 mg/kg and 0.5 mg/kg methylphenidate BID. All treatments were randomized and administered for a minimum of 7 days. Results indicated improvements related to medication were obtained on measures of cognitive tests of attention and as assessed by parent rating scales. Cognitive tests of impulsivity presented an equivocal picture of sensitivity to medication treatment. Attentional abilities in an interactive setting indicated a medication response from Baseline measures only and the degree to which this effect was augmented by Placebo treatment was unclear. That is, there was some evidence that parental expectancies played a role in these measures. No changes were obtained with respect to the children's tendency to comply with parental requests. Side effects were not significantly increased with medication treatment. Parental skills appeared unaffected by the child's medication status. However, parental style appeared to become more positive especially following treatment with the higher dose. Although the stress reported to be experienced by the parent decreased following treatment, the response was non-specific, that is, not related to the medication status of the child. Not surprisingly, clinical change analyses showed parent ratings were more effective than the cognitive task in picking up the number of children who had responded favourably to medication. Parents rated many children as having improved or normalized following treatment with both doses. Similar rates of positive change were obtained with respect to negative behaviours. This investigation into the efficacy of MPH in the treatment of very young children diagnosed with ADHD indicated that it was effective in allievating symptoms of inattention as assessed by laboratory tests and by parent rating scales. Although parents rated negative behaviours as having decreased as a function of medication, these behavioural changes were not detected during the interactive tasks In general, parent-child tasks did not demonstrate the effectiveness of medication in changing the parents' behaviours or the parent-child dynamic.
Keywords: Health Sciences, Mental Health.